2021
DOI: 10.1097/hco.0000000000000929
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of cardiac contractility modulation in heart failure treatment

Abstract: Purpose of reviewHeart failure often progresses despite optimal medical and device therapies, and advanced mechanical circulatory support has limited availability and substantial associated morbidity. Cardiac contractility modulation (CCM) provides nonexcitatory stimulation to ventricular myocardium which increases cardiac contractility without increasing oxygen demand. This review describes the emerging role of CCM in heart failure treatment. Recent findingsThe FIX-HF-5C2 study demonstrated similar safety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
9
0
1
Order By: Relevance
“…The Optimizer unit was then attached to the leads and located in the pocket ( Figure 2 ). The Optimizer pulse generator needs manual transcutaneous recharging by the patient: routine recharging is done weekly and needs about 1 h to complete ( 11 ). In our case, the CCM therapy was scheduled for 10 h/day ( Figure 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Optimizer unit was then attached to the leads and located in the pocket ( Figure 2 ). The Optimizer pulse generator needs manual transcutaneous recharging by the patient: routine recharging is done weekly and needs about 1 h to complete ( 11 ). In our case, the CCM therapy was scheduled for 10 h/day ( Figure 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…The FIX‐HF‐5C trial compared the previous three‐lead system with the two‐lead Optimizer device, demonstrating similar safety and efficacy profiles 66 . This study also found that CCM reduced NYHA class III symptoms in patients with mild–moderate LV dysfunction (EF 25–45%) 66 .…”
Section: Related Clinical Studiesmentioning
confidence: 72%
“…Impulse Dynamics received FDA approval in 2019 for patients with ejection fraction between 25% and 40% with continued NYHA class III symptoms despite guideline directed medical therapy (GDMT) who do not have an indication for CRT. A recent review highlighted improvements in CCM therapy [19 ▪ ]. An observational analysis in the MAINTAINED study population showed relatively greater improvement in ejection fraction at 3 and 5 years postdevice implant in nonischemic versus ischemic patients [20].…”
Section: Pacing-directed Therapiesmentioning
confidence: 99%